Motor current signature analysis and negati ve sequence current based stator winding short fault detection in an induction motor (2011)
In this paper, negative sequence analysis and motor current signature analysis (MCSA) based approaches are applied to perform short fault detection of a single phase winding in an induction motor. The fault detection is carried out using the negative sequence analysis and spectral analysis of current signals. An experimental analysis is presented, showing the advantages and drawbacks for each methodimplemented. Tests are performed in a 2 Hp induction motor dedicated to this type of study. Experimental results show variations in the faultindicator in both methods when the motor is running under different load conditions. Although the negative sequence current method demands simultaneous three phase current sensing, it presents better performance for short fault detection and provides a fault severity level estimation.